Peranan Pasta Manggis terhadap Kesembuhan Ulkus Akibat Luka Gores (Pemeriksaan Histo Patologi Anatomi) - Lanny Sunarjo; Salikun Salikun; Hermien Rimbyastuti (Poltekkes Kemenkes Semarang, 2015)
The objective of study is to know impact of pasta rind mangosteen applied topically towards gradation of traumatic ulcer healing reviewed HPA. The method was experimental research, pre-posttest control group design, randomized sampling technique with total sampel of 12 Male Wistar rats divided into 2 groups @ 6 applied pasta rind mangosteen and the other used standard gel. Some rats in each group euthanized day 3rd, 7th and 10th. The gradation of ulcer healing day 3rd, 7th and 10th showed decrease in both PMN and macrophage and increase fibroblast cells. Based on statistical test day 10th, there was no difference amount of PMN, macrophage and fibroblast cells between standard gel and pasta rind mangosteen. In conclusion usage of pasta rind mangosteen topical could be safe, reduced inflammation and accelerated of traumatic ulcer healing.